2009
DOI: 10.1093/cercor/bhp224
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Failure: Feedback-Related Negativity Predicts Motor Learning Efficiency

Abstract: Learning from past mistakes is of prominent importance for successful future behavior. In the present study, we tested whether reinforcement learning signals in the brain are predictive of adequate learning of a sequence of motor actions. We recorded event-related potentials (ERPs) while subjects engaged in a sequence learning task. The results showed that brain responses to feedback (the feedback-related negativity [FRN]) predicted whether subjects learned to avoid an erroneous response the next time this act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
67
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 24 publications
6
67
0
Order By: Relevance
“…Our finding that the failure-related Ne/ERN enhancement was accompanied by higher posterror accuracy supports this view. Similar conclusions have been drawn from previous studies demonstrating that activity in the medial prefrontal error-processing system predicted the correctness of future responses (Hester, Barre, Murphy, Silk, & Mattingley, 2008;van der Helden, Boksem, & Blom, 2010). Moreover, findings by Frank et al (2005) suggest a specific relation between Ne/ERN amplitude and a bias to learn more from bad than from good choices.…”
Section: Discussionsupporting
confidence: 88%
“…Our finding that the failure-related Ne/ERN enhancement was accompanied by higher posterror accuracy supports this view. Similar conclusions have been drawn from previous studies demonstrating that activity in the medial prefrontal error-processing system predicted the correctness of future responses (Hester, Barre, Murphy, Silk, & Mattingley, 2008;van der Helden, Boksem, & Blom, 2010). Moreover, findings by Frank et al (2005) suggest a specific relation between Ne/ERN amplitude and a bias to learn more from bad than from good choices.…”
Section: Discussionsupporting
confidence: 88%
“…Results from correlational analyses showed that the amplitude of the ERN tended to increase with the number of learning blocks. In a trial-and-error motor learning task, the ERN amplitude following a feedback (commonly referred to as the feedback-related negativity; FRN) has been shown to predict motor learning efficiency [26]. In this study, an enhanced FRN was found for errors that were subsequently adjusted compared to errors that were repeated.…”
Section: Introductionmentioning
confidence: 66%
“…For example, a dieter facing a delicious dessert in an isolated occasion is less likely to identify the conflict between her ultimate goal (i.e., losing weight) and the tempting high-caloric food, than when considering dessert for multiple similar future consumptions [100]. Thus, our modified version of the Stop-signal task might have induced subjects to face, in a brief lapse of time, multiple error signals and conflict concerning a specific food, thereby priming avoidance motivation for events associated with negative outcomes and more self-controlled decisions [39][40], [46][47].…”
Section: Discussionmentioning
confidence: 99%
“…As aversive events, errors produce a negative neural wave (error-related negativity, ERN; [41], [42]), generated in the anterior cingulate cortex (ACC) (e.g., [43]), both when subjects become aware of having committed a mistake and when they are not explicitly aware of making the error [43][44]. It has been suggested that the ERN may signify affective processing in response to errors [45], and individuals with larger ERNs showed enhanced avoidance learning for events associated with negative outcomes ([39][40], [46]; see also [47]). …”
Section: Introductionmentioning
confidence: 99%